Hyper-SUMOylation of ERG Is Essential for the Progression of Acute Myeloid Leukemia - Chen, Xu; Qin, Yuanyuan; Zhang, Zhenzhen; Xing, Zhengcao; Wang, Qiqi; Lu, Wenbin; Yuan, Hong; Du, Congcong; Yang, Xinyi; Shen, Yajie; Zhao, Biying; Shao, Huanjie; et al. (Frontiers in Molecular Biosciences, 2021)
Leukemia is a malignant disease of hematopoietic tissue characterized by the dedifferentiation and malignant proliferation of immature hematopoietic precursor cells in bone marrow. ERG (ETS-related gene) is an important member of the E26 transformation-specific (ETS) transcription factor family that plays a crucial role in physiological and pathological processes. However, the role of ERG and its modification in leukemia remains underexplored. In the present study, we stably knocked down or overexpressed ERG in leukemia cells and observed that ERG significantly promotes the proliferation and inhibits the differentiation of AML (acute myeloid leukemia) cells. Further experiments showed that ERG was primarily modified by SUMO2, which was deconjugated by SENP2. PML promotes the SUMOylation of ERG, enhancing its stability. Arsenic trioxide decreased the expression level of ERG, further promoting cell differentiation. Furthermore, the mutation of SUMO sites in ERG inhibited its ability to promote the proliferation and inhibit the differentiation of leukemia cells. Our results demonstrated the crucial role of ERG SUMOylation in the development of AML, providing powerful targeted therapeutic strategies for the clinical treatment of AML.